The politicization of climate change: problem or solution?. (17th May 2016) - Pepermans, Yves; Maeseele, Pieter
Abstract : In the academic literature, two perspectives can be distinguished regarding the climate debate. The dominant consensus‐building perspective problematizes the politicization of climate change as an important barrier to climate action and resultantly sets out to develop depoliticizing communication strategies which foster social consensus and public engagement. In contrast to this, the critical debate perspective problematizes climate change's capture in a depoliticized consensus and calls for its repoliticization to revive democratic debate and citizenship. The aim of this article is twofold. First, we will distinguish both perspectives on the basis of their diverging problem diagnoses and recommendations. Second, we will argue how only the critical debate perspective provides the tools for transformative socioecological change based on both democratic debate and democratic citizenship. We conclude by discussing how this divergence is reflective of a larger split in the social sciences between problem‐solving and critical theory and how social scientists could contribute to democratic debate and citizenship. WIREs Clim Change 2016, 7:478–485. doi: 10.1002/wcc.405 This article is categorized under: Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge